2018
DOI: 10.1097/mph.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Vein Catheter is an Important Risk Factor for Catheter-related Thrombosis in (Near-)term Neonates

Abstract: Central venous catheters (CVCs) in neonates are associated with an increased risk of thrombosis. Most reports focus on umbilical venous catheters (UVCs) and peripherally inserted central catheters (PICCs), whereas data available on femoral venous catheters (FVCs) are limited. We performed a retrospective cohort study in all neonates (gestational age ≥34 wk) with CVCs. The primary outcome was the occurrence of thrombosis in CVCs. The secondary outcomes were possible risk factors for thrombosis, the thrombotic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
2
8
0
2
Order By: Relevance
“…[8][9][10] Thrombosis incidence rates ranging from 0.8 to 14.9 % and incidence density rates from 0.4 to 13.2 ‰ catheter-days have been reported. [11][12][13] The incidence rates observed in this study when considering only the onset of clinical signs for thrombosis diagnosis were consistent with the lowest values reported in the bibliography; however, this values increased at least 5 times when using a systematic screening protocol based on imaging tests.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[8][9][10] Thrombosis incidence rates ranging from 0.8 to 14.9 % and incidence density rates from 0.4 to 13.2 ‰ catheter-days have been reported. [11][12][13] The incidence rates observed in this study when considering only the onset of clinical signs for thrombosis diagnosis were consistent with the lowest values reported in the bibliography; however, this values increased at least 5 times when using a systematic screening protocol based on imaging tests.…”
Section: Discussionsupporting
confidence: 88%
“…18,19 Catheters may favor the formation of thrombi in newborn infants through damage to the vessel wall, disruption of blood flow in small-diameter vessels, type of catheter used, and infusion of hyperosmolar substances, among other mechanisms. 3 Dubbink-Verheij et al, 12 reported a lower incidence of thrombosis when using umbilical and peripherally inserted catheters compared to femoral catheters in newborn infants with a gestational age ≥ 34 weeks. In a systematic review and metaanalysis on CVC-related venous thrombosis in children, Vidal et al, 20 also observed a lower frequency of thrombosis associated with the use of umbilical and peripherally inserted catheters.…”
Section: Discussionmentioning
confidence: 99%
“…However, CVCs are frequently needed in sick infants and other types of central catheters than UVCs are associated with thrombosis as well. Replacement of the UVC by another type of catheter may not necessarily lead to less complications 6 13 22 26 27…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Se han reportado tasas de incidencia de trombosis que varían del 0,8 % al 14,9 % y de densidad de incidencia entre el 0,4 y el 13,2 ‰ días/catéter. [11][12][13] Las incidencias halladas en nuestro trabajo utilizando solo la aparición de signos clínicos para el diagnóstico de trombosis se encontraron junto con los valores más bajos reportados por la bibliografía; sin embargo, estos valores aumentaron, al menos, 5 veces utilizando un protocolo de búsqueda sistemática con imágenes.…”
Section: Discussionunclassified